The Criminal Hygiene Approuch in Preventing Sexual Violence Crimes Against Potential Victims - Permana, Ajeng; Kuswandi (Indonesian Journal of Law and Justice, 2025)
This study aims to analyse the effectiveness of the Criminal Hygiene Approach in preventing sexual abuse crimes against potential victims, particularly vulnerable groups such as children, women, and the elderly. The research focuses on crime prevention efforts through improving social and environmental conditions that are considered to have a significant influence on the emergence of sexual abuse crimes. The research method used is a normative juridical approach supported by an empirical juridical approach, conducted through literature studies, analysis of court decisions, and criminological studies relevant to the prevention of sexual crimes. The results of the study show that the application of the principles of Criminal Hygiene plays an important role in creating a safe and preventive social environment, including through strengthening education, increasing legal literacy, social awareness, and continuous environmental monitoring. Analysis of sexual abuse cases in the Tangerang and Kulon Progo areas revealed that these crimes were influenced by a closed social environment, low intensity of social interaction, weak informal social control, and limited access to protection mechanisms for vulnerable groups. In addition, this study found various obstacles in the implementation of the Criminal Hygiene Approach, such as the tendency of victims to remain silent due to fear and social stigma, weak coordination between authorised institutions, and low levels of public awareness and participation in prevention efforts. Therefore, this study emphasises that strengthening the Criminal Hygiene Approach requires continuous synergy between families, communities, and formal institutions so that protection for potential victims can be carried out effectively, comprehensively, and in an integrated manner.